Basonuclin-1 modulates epithelial plasticity and TGF-β1-induced loss of epithelial cell integrity - Feuerborn, Alexander; Gretz, Norbert (Oncogene, 2015)
Transforming growth factor-β1 (TGF-β1) is a multifunctional cytokine and critically involved in the progression of a variety of cancers. TGF-β1 signaling can impair tumor development by its anti-proliferative and pro-apoptotic features. In contrast, it may actively promote tumor progression and cancer cell dissemination by inducing a gradual switch from epithelial towards mesenchymal-like cell features (EMT-like), including decreased intercellular adhesion. Here, we show that expression of the transcription factor Basonuclin-1 (Bnc1) modulates TGF-β1-induced epithelial dedifferentiation of mammary epithelial cells. RNAi-mediated repression of Bnc1 resulted in enhanced intercellular adhesion and strongly impaired TGF-β1-dependent sheet disintegration and cell scattering. In contrast, forced expression of Bnc1 modifies plasma membrane/cytoskeletal dynamics and seemingly interferes with the initiation of sustainable cell-cell contacts. Follow-up analyses revealed that Bnc1 affects the expression of numerous TGF-β1-responsive genes including distinct EMT-related transcription factors, some of which modulate the expression of Bnc1 themselves. These results suggest that Bnc1 is part of a transcription factor network related to epithelial plasticity with reciprocal feedback-loop connections on which Smad-factors integrate TGF-β1 signaling. Our study demonstrates that Bnc1 regulates epithelial plasticity of mammary epithelial cells and influences outcome of TGF-β1 signaling.
Gesehen am 24.08.2017